KADAR ZAT GIZI DAN CITA RASA HASIL FERMENTASI CAIR IKAN RUCAH - Uken S.S. Soetrisno; Rossi Rozanna; N. Imanningsih; L. Pasaribu (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1998)
Teri rucah (Stolephorus Spec.) and udang rucah (Atydal Spec.) as by-catch fishes had been used as basic materials in liquified fermentation process. The results were evaluated for its contribution to improve nutrient content and to add more variation on fermentation product for consumer choice. The proportion of basic materials to salt and water were varied depending on the kind of fish and the optimum values were chosen. Fermented teri rucah needed addition of one part of salt and two parts of water, or one part of salt and one and half parts of water; fermented udang rucah needed addition of one part of salt and one part of water, or nine-tenth parts of sah and one-tenth parts of water, forevery three part of basic material. All fermented products were analyzed for proximate nutrient contentand vitamin B-12 content Fermented teri rucah was higher in protein and vitamin B-12 content compared to that of udang rucah. In general liquefied fermentation increased vitamin B-12 content by 2 to 4 times. Incorporation of the produds into traditional cooking recipes need to be explored and socially marketed.